Genetic Dissection of the mamAB and mms6 Operons Reveals a Gene Set Essential for Magnetosome Biogenesis in Magnetospirillum gryphiswaldense - Lohße, Anna (American Society for Microbiology, 2014)
Biosynthesis of bacterial magnetosomes, which are intracellular membrane-enclosed, nanosized magnetic crystals, is controlled by a set of >30 specific genes. In Magnetospirillum gryphiswaldense, these are clustered mostly within a large conserved genomic magnetosome island (MAI) comprising the mms6, mamGFDC, mamAB, and mamXY operons. Here, we demonstrate that the five previously uncharacterized genes of the mms6 operon have crucial functions in the regulation of magnetosome biomineralization that partially overlap MamF and other proteins encoded by the adjacent mamGFDC operon. While all other deletions resulted in size reduction, elimination of either mms36 or mms48 caused the synthesis of magnetite crystals larger than those in the wild type (WT). Whereas the mms6 operon encodes accessory factors for crystal maturation, the large mamAB operon contains several essential and nonessential genes involved in various other steps of magnetosome biosynthesis, as shown by single deletions of all mamAB genes. While single deletions of mamL, -P, -Q, -R, -B, -S, -T, and -U showed phenotypes similar to those of their orthologs in a previous study in the related M. magneticum, we found mamI and mamN to be not required for at least rudimentary iron biomineralization in M. gryphiswaldense. Thus, only mamE, -L, -M, -O, -Q, and -B were essential for formation of magnetite, whereas a mamI mutant still biomineralized tiny particles which, however, consisted of the nonmagnetic iron oxide hematite, as shown by high-resolution transmission electron microscopy (HRTEM) and the X-ray absorption near-edge structure (XANES). Based on this and previous studies, we propose an extended model for magnetosome biosynthesis in M. gryphiswaldense.